2021
DOI: 10.3390/land10020189
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions from Forest Soils Reduced by Straw Biochar and Nitrapyrin Applications

Abstract: Forestlands are widely distributed in the dominantly agricultural landscape in western Canada, and they play important ecological functions; such forestlands (e.g., shelterbelts) accumulate soil organic matter and may receive a substantial amount of nitrogen in the form of surface and subsurface runoff from adjacent croplands and become a significant source of emissions of greenhouse gases (GHGs) such as CO2, N2O, and CH4. Biochar and nitrapyrin applications could potentially mitigate GHG emissions, but their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Meanwhile, Tang et al [10] found that CO 2 emissions increased with the increasing biochar addition ratio. However, some investigations contradict the conclusions shown above [13][14][15][16]. For example, Sakin et al [16] found that biochar addition reduced soil CO 2 emissions, and the CO 2 emissions were lowest at the highest addition ratio.…”
Section: Introductionmentioning
confidence: 96%
“…Meanwhile, Tang et al [10] found that CO 2 emissions increased with the increasing biochar addition ratio. However, some investigations contradict the conclusions shown above [13][14][15][16]. For example, Sakin et al [16] found that biochar addition reduced soil CO 2 emissions, and the CO 2 emissions were lowest at the highest addition ratio.…”
Section: Introductionmentioning
confidence: 96%
“…However, some studies have indicated that the effect of biochar is inconsistent and have reported a neutral or slight increase in N 2 O emissions [21][22][23][24]. For example, the incorporation of high C/N ratio biochar can suppress N 2 O emissions because available soil N is immobilized [25].…”
Section: Introductionmentioning
confidence: 99%